Coming of Age in Quebec: Reviving the Nation’s “Cinéma orphelin” - Charles, Morgan (Nouvelles vues, 2011)
The current essay offers a critical reflection on the contemporary resurgence of Quebec’s “cinéma orphelin,” or orphan cinema, through an analysis of the films C’est pas moi, je le jure! (Philippe Falardeau, 2008) and Maman est chez le coiffeur (Léa Pool, 2008). Given that films such as these are typically read allegorically as indicative of a particular national imaginary, I argue that these two films from 2008 reflect broader shifts within the cultural memory of Quebec. Their specific interventions reveal a will to move away from earlier articulations of its history as both exceptional and characterized by a history of trauma and rupture.